Pengalaman Muhammadiyah Membumikan Nilai-nilai Pluralisme - Biyanto, Biyanto (Program Pascasarjana UIN Sunan Ampel Surabaya, 2013)
This article deals with the issue of religious pluralism in the view of the leading authorities within Muhammadiyah. The paper argues that the scholars of the organization develop a unique view of religious pluralism in line with the vision of the founding fathers. Apart from some âdiscursive distortionâ that these scholars might have undergone in the process of developing the discourse, their view deserves some appreciation for its depth and originality. The paper tries to show that there is indeed a tension between the cadres of the organization on the problem at hand. To dwell into this tension, the paper distinguishes between two major groups within the organization, namely that which accepts the notion of religious pluralism, and that which rejects it. The former includes such well-known scholars as Syafii Maarif, Amin Abdullah, Abdul Munir Mulkhan, and Moeslim Abdurrahman, whereas the latter includes the preachers and mosque-activists. Apart from these two groups, the paper will also look at the particular role that the Muhammadiyahâs Youth Movement has played in discourse-development among the members of the organization. Hence, the areas that the paper will cover include those that have been well-represented by the most admitted elements of the organization.